Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - Chapter Test: 33

Answer

a) a=$(x-2)^{2}$ b= 3 b) (x-5)(x+1)

Work Step by Step

A) We use the formula for the difference of squares to apply to this question. The difference of squares formula is: $(a-b) (a+b) = a^{2} - b^{2}$ = $(x-2)^{2}$ - 9 *** Take the square root of 9 which is 3. Becuase 3 × 3= 9 = $(x-2)^{2}−3^{2}$ In the given formula let $(x-2)^{2}$ represents a and 3 represents b. B) a= $(x-2)^{2}$ b= 3 The difference of squares formula is: $ (x-2)^{2} - 3^{2}$ = ((x-2)-3) ((x-2)+3) (x-2-3)(x-2+3) (x-5)(x+1)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.